2022
DOI: 10.1021/acs.inorgchem.2c03665
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Studies of Ruthenium Complexes Bearing Z-Acceptor Aluminum-Based Phosphine Pincer Ligands

Abstract: Reaction of [Ru(C6H4PPh2)2(Ph2PC6H4AlMe(THF))H] with CO results in clean conversion to the Ru−Al heterobimetallic complex [Ru(AlMePhos)(CO)3] (1), where AlMePhos is the novel P–Al(Me)–P pincer ligand (o-Ph2PC6H4)2AlMe. Under photolytic conditions, 1 reacts with H2 to give [Ru(AlMePhos)(CO)2(μ-H)H] (2) that is characterized by multinuclear NMR and IR spectroscopies. DFT calculations indicate that 2 features one terminal and one bridging hydride that are respectively anti and syn to the AlMe group. Calculations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Finally, the calculated ellipticities for the M-C bonds showed that the ellipticities average values of Co-Cp* interactions 1.317 are in most cases higher than the Ru-Cp bonds (ranging from 0.647-0.992). Large calculated values for the ellipticities indicated that the M-C bonds have a л character and are consistent with earlier research based on the MO theory 41 . Delocalization Indices.…”
Section: M-cp Interactions In Clustersupporting
confidence: 90%
“…Finally, the calculated ellipticities for the M-C bonds showed that the ellipticities average values of Co-Cp* interactions 1.317 are in most cases higher than the Ru-Cp bonds (ranging from 0.647-0.992). Large calculated values for the ellipticities indicated that the M-C bonds have a л character and are consistent with earlier research based on the MO theory 41 . Delocalization Indices.…”
Section: M-cp Interactions In Clustersupporting
confidence: 90%
“…-Cp* interactions (1.561) are in most cases lower than the Ru-Cp bonds (1.258-2.031). The M-C bonds have a л character, according to computed large values for the ellipticities, which is compatible with past findings based on the MO theory43 .…”
supporting
confidence: 92%
“…These numbers are consistent with the values that have previously been published in the literature 42 . Finally, the calculated ellipticities for the M-C bonds showed that the ellipticities average The delocalization index, δ(A, B), is one of the best tools to estimate the number of delocalized electron pairs between two atoms 43,44 . Therefore, as listed in Table 2, we calculated these indices as a tool to analyze a multicenter bonding in this cluster from one side and to describe different M…M interaction modes from another side 38 .…”
Section: M-cp Interactions In Clustermentioning
confidence: 99%
“…To the best of our knowledge, photolytic reactivity is limited to two examples involving the addition of H 2 to Ru-Zn and Ru-Al heterometallic complexes. 11,12 These ndings contrast the rich chemistry of single-site transition metal complexes, where examples of photochemical H 2 activation are more common. Under photolytic conditions, 18-electron transition metal carbonyl complexes are prone to ligand dissociation to generate coordinatively unsaturated intermediates that can react with H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, photolytic reactivity is limited to two examples involving the addition of H 2 to Ru–Zn and Ru–Al heterometallic complexes. 11,12…”
Section: Introductionmentioning
confidence: 99%